Complete Closed Genome Sequences of Salmonella enterica subsp. enterica Serotypes Anatum, Montevideo, Typhimurium, and Newport, Isolated from Beef, Cattle, and Humans - Harhay, Dayna M. (Genome Announc, 2016)
Salmonella enterica spp. are a diverse group of bacteria with a wide range of virulence potential. To facilitate genome comparisons across this virulence spectrum, we present eight complete closed genome sequences of four S. enterica serotypes (Anatum, Montevideo, Typhimurium, and Newport), isolated from various cattle samples and from humans.